2013
DOI: 10.1021/np400497f
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated Coumarins from the Polypore Mushroom Fomitopsis officinalis and Their Activity against Mycobacterium tuberculosis

Abstract: An EtOH extract of the polypore mushroom, Fomitopsis officinalis afforded two new naturally occurring chlorinated coumarins which were identified as the previously synthesized compounds, 6-chloro-4-phenyl-2H-chromen-2-one (1) and ethyl 6-chloro-2-oxo-4-phenyl-2H-chromen-3-carboxylate (2). The structures of the two isolates were deduced ab initio by spectroscopic methods and confirmed by chemical synthesis. In addition, an analogue of each was synthesized as of 7-chloro-4-phenyl-2H-chromen-2-one (3) and ethyl 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 26 publications
2
29
0
4
Order By: Relevance
“…Based on the observations obtained from the four molecules in assays to Mycobacterium tuberculosis (anti-TB), the authors concluded that the anti-TB activity is higher when the ethyl ester introduces chlorine in position 6, while coumarins with a chlorine substituted at the 7-position are less active (Hwang et al 2013). Mammalian cell cytotoxicity using Vero cells was observed by the authors at a similar concentration that causes significant inhibition against M. tuberculosis and Mycobacterium bovis.…”
Section: Fungal Coumarins Basidiomycetes Fungimentioning
confidence: 95%
See 3 more Smart Citations
“…Based on the observations obtained from the four molecules in assays to Mycobacterium tuberculosis (anti-TB), the authors concluded that the anti-TB activity is higher when the ethyl ester introduces chlorine in position 6, while coumarins with a chlorine substituted at the 7-position are less active (Hwang et al 2013). Mammalian cell cytotoxicity using Vero cells was observed by the authors at a similar concentration that causes significant inhibition against M. tuberculosis and Mycobacterium bovis.…”
Section: Fungal Coumarins Basidiomycetes Fungimentioning
confidence: 95%
“…This compound is used as a choleretic to improve bile secretion and regulate the pressure of the bile duct to ease inflammation and adjust liver function (Wang et al 2007). Hwang et al (2013) isolated two new coumarins (Fig. 2), 6-chloro-4-phenyl-2H-chromen-2-one (1) molecular formula C 15 H 9 ClO 2 , with 0.5 mg when isolated, and ethyl 6-chloro-2-oxo-4-phenyl-2H-chromen-3-carboxylate, with 0.2 mg when isolated, from an EtOH extract of the mushroom Fomitopsis officinalis, aimed for the application in tuberculosis treatment (anti-TB).…”
Section: Fungal Coumarins Basidiomycetes Fungimentioning
confidence: 99%
See 2 more Smart Citations
“…Positive results were also obtained with extracts of ethanol, hexane and water of F. lilacinogilva against B. cereus, Escherichia coli and S. aureus (Bala et al 2011(Bala et al , 2012. Ethanolic compounds from F. officinalis exhibited bioactivity against Mycobacterium tuberculosis (Hwang et al 2013).…”
Section: Discussionmentioning
confidence: 99%